Comic books: Experience report in an art studio (Research, Society and Development, 2024)
The study aims to describe the language characteristics of comic books created in an art studio. A descriptive method with a qualitative approach was employed, using the experience report technique. Data was gathered from an art studio in Parintins, Amazonas, Brazil. It was observed that the thematic focus of the work at the studio revolves around depicting the Amazon people through comic books. Therefore, culture is spread in order to positively influence art throughout the region, considering the description of the artistic process that passes through the hands of studio members who are trained by the creator and local coordinator, thus making it an essential part of comic book construction. The studio attracts visual arts students, individuals from various artistic backgrounds, and members of socio-cultural movements and Non-Governmental Organizations with cultural interests. It is therefore concluded that comic books created at the studio reflect an engagement with the Amazonian scenario and the culture of the people in Parintins, serving as a means to disseminate knowledge and narrate stories related to the original peoples, caboclos, and riverside dwellers of the Amazon region.